OPERATORS ON THE BESOV SPACES OF HOLOMORPHIC FUNCTIONS ON THE UNIT BALL IN $\mathbb{C}^n$ - Harutyunyan, A.V.; Lusky, W. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2017)
In the present paper we consider the Toeplitz-$T_{\bar{h}}^{ α}$ and differentiation-$D^δ $ operators on the Besov spaces $B_p(β)$ for all $0< p
Keywords: weighted Besov spaces, unit ball, projection